PENGARUH PROFITABILITAS, LEVERAGE, TIPE AUDITOR, KONSENTRASI KEPEMILIKAN SAHAM DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2012-2014) - Septi Zaerina Eliza R., 12.05.52.0040; Indarti, MG Kentris (Students Journal of Accounting and Banking, 2016)
This research aims to test and analyze the influence of profitability, leverage, auditor type, ownership concentration and firm size on the intellectual capital disclosure. This research was conducted at the Indonesian Stock Exchange by using go public manufacturing company as the unit of analysis.Â The population of this research are all manufacturing companies that listed in Indonesian Stock Exchange (IDX) during 2012-2014. The sample was selected using purposive sampling method and obtained 270 companies being sampled. This research analyzes the companyâs annual report using the method of content analysis. Data analysis used descriptive statistics, classical assumption test, and multiple linear regression analysis.Â The result of this study showed that profitability and firm size positive significantly influence to the intellectual capital disclosure. Meanwhile, leverage, auditor type and ownership concentration had no effect to the intellectual capital disclosure.Keywords: Intellectual Capital Disclosure, Profitability, Leverage, Auditor Type, Ownership Concentration, Firm Size